Manda eu! um estudo experimental dos antecedentes da intenção de compartilhar fake news - Sousa, Eduardo Mesquita de (2022)
Fake news is the production of news that are completely false or that contains deliberate misleading elements that are intentionally incorporated into the content or context. In general, the purpose of fake news is to spread information no proven veracity, in order to harm something or someone. Another reason for producing fake news to increase the flow of visits to “malicious” websites, this communication strategy being called “click bait”. These contents can harm not only public sectors, but also private organizations. That said, the proposed objective for this research is to investigate how and when the news source can explain the intention to share a fake news. This study is empirical and positivist, with a quantitative approach and experimental strategy. The phenomenon of fake news, enhanced by social networks, is relatively new and little has been addressed in studies of consumer behavior, being this study relevant for the generation of knowledge in the area. This research aims to contribute to the understanding of the spread of fake news, and can help managers, both in the private and public sectors, in the fight against this phenomenon that has been harmful to society. The results of the studies showed that a source can persuade news consumers, even if it is a fraudulent news, to deceive consumers. This path can be explained through the belief in the veracity of the news. In addition, the dissemination of fake news is enhanced for individuals in need of social approval, as long as the news is perceived as relevant to the others.